Investigating the relationship between AGN activity and stellar mass in zCOSMOS galaxies at 0 - Vitale, M; Mignoli, M; Cimatti, A; Lilly, S; Carollo, C; Contini, T; Kneib, J; Fevre, O; Mainieri, V; Renzini, A; Scodeggio, M; Zamorani, G; et al. (2013)
We investigate the link between AGN activity, star-formation and stellar mass of the host galaxy at 0<z<1, 20k="" a="" above="" aging="" agn="" an="" and="" at="" bins="" classification.="" contributes="" create="" data="" diagnostic="" diagrams="" divided="" emission-line="" evolution="" existing="" exploited="" extension="" for="" found="" from="" galaxies="" galaxies.="" galaxy="" host.="" improved="" in="" indication="" intermediate="" leading="" light="" log="" looking="" m_*="" m_sun="" mass="" mass-redshift="" n.="" obtain="" of="" on="" provides="" redshifts.="" role="" s="" sample="" separate="" several="" shed="" show="" signatures="" spectra="" spectroscopic="" stacked="" star-forming="" stellar="" studies="" the="" this="" to="" total="" traces="" used="" we="" with="" work="" z<0.1="" z<1.="" zcosmos="">10.2 threshold. Moreover, the stellar populations of AGN hosts are found to be older with respect to star-forming and composites galaxies. This could be due to the the tendency of AGN to reside in massive hosts. The dependence of the AGN classification on the stellar mass is in agreement with what has been already found in previous studies. It is consistent with, together with the evidence of older stellar populations inhabiting the AGN-like galaxies, the downsizing scenario. In particular, our evidence points to an evolutionary scenario where the AGN-feedback is capable of quenching the star formation in the most massive galaxies. Therefore, the AGN-feedback is the best candidate for initiating the passive evolutionary phase of galaxies.</z<1,>